2016
DOI: 10.1186/s40623-016-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

Crust and uppermost mantle structure of the Kyushu-Palau Ridge, remnant arc on the Philippine Sea plate

Abstract: We acquired 27 wide-angle seismic profiles to investigate variation in crustal structure along the Kyushu-Palau Ridge (KPR), a 2600-km-long remnant island arc in the center of the Philippine Sea plate; 26 lines were shot across the strike of the KPR at 13°-31°N, and one was shot along the northernmost KPR. The derived P-wave velocity (Vp) models show that the KPR has a crustal thickness of 8-23 km, which is thicker than the neighboring backarc basin oceanic crusts of the West Philippine Basin to the west and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…1 and 3 ). The KPR plays a key role in the volcano-tectonic evolution of the SW Japan arc, as this forms a boundary between a younger (< 25 Ma) and an older (> 50 Ma) oceanic lithosphere and is composed of buoyant arc crust with the middle crust exhibiting seismic velocity similar to that of the bulk continental crust 34 .
Figure 3 Positions of the Kyushu-Palau Ridge (KPR) at present, 3, and 14 Ma arranged by subduction of the PHS plate shown by arrows.
…”
Section: Resultsmentioning
confidence: 99%
“…1 and 3 ). The KPR plays a key role in the volcano-tectonic evolution of the SW Japan arc, as this forms a boundary between a younger (< 25 Ma) and an older (> 50 Ma) oceanic lithosphere and is composed of buoyant arc crust with the middle crust exhibiting seismic velocity similar to that of the bulk continental crust 34 .
Figure 3 Positions of the Kyushu-Palau Ridge (KPR) at present, 3, and 14 Ma arranged by subduction of the PHS plate shown by arrows.
…”
Section: Resultsmentioning
confidence: 99%
“…The V p model of ECr31, along the arc line, reveals a typical island structure, the same as the Japan arc compiled by Iwasaki and Sato (2009). A high V p of around 7.2 km/s at the bottom of the lower crust beneath intra-oceanic island arcs, such as the Izu-Ogasawara island arc and the Kyushu-Palau Ridge (e.g., Nishizawa et al 2006Nishizawa et al , 2016, was not found in the Ryukyu arc. None of the arc crusts of the Japan Islands have such a high V p at the bottom of the lower crust, which might indicate differences in the evolution tectonics between the intra-oceanic island arcs and the Japan island arcs.…”
Section: Ryukyu Island Arcmentioning
confidence: 96%
“…The results show that S wave source locations for the three typhoons are almost same despite of the slightly different source regions. The S wave source region is associated with the KPR that is a 2,600‐km‐long unit extending north‐south with steep bathymetry, bounded by Parece Vela Basin (PVB) to the east and by the WPB to the west (Nishizawa et al, 2016). Comparing the S wave source regions with the geological structures, we find that the S wave microseisms are not only generated in the region with steep topography but also in the flat seafloor region.…”
Section: Discussionmentioning
confidence: 99%